(untitled) (Medicine Today, 2023)
Introduction: Migration is a process of social change where an individual, alone or accompanied by others, because they may have different purposes especially for study, leaves one geographical area for a prolonged stay. Prolonged detention is seen to have impacted adversely on physical and mental health. The aim of this study was to evaluate the physical and psychological problems associated with the migration of foreign students compared to local ones. Materials and Methods: TA case-control study was conducted from March 2017 to August 2022 on the students of five different countries. A total of 280 students were enrolled in this study from Dhaka Dental College in Dhaka city. They were divided into case and control groups. To determine the physical and mental health of them, different parameters were used. Results: Total female-migrants were 3.24 times higher than male-migrants. Kashmir-migrants (47.14%) were higher whereas Bhutan-migrants (0.71%) were lowest in number. Psychological factors like depression, Insomnia, loneliness, and stress were more common in all migrants, particularly in the female. Physical health issues like diarrhea, food poisoning were common in males, however, urinary tract infection and skin problems were of insignificant magnitude in female-migrants. Conclusion: Migrant students’ physical and mental health is heavily affected by the adopted country’s environment, culture, tradition, language, food habits, and so on. The intensity of the psychological problem has been found to be higher among some migrant groups. Similarly, physical problems such as allergic reactions, respiratory diseases were the most common problems experienced by them. Medicine Today 2023 Vol.35(1): 49-51